Depression and Older Adults - Heidi Liss Radunovich (EDIS, 2007)
FCS-8848, a 2-page fact sheet by Heidi Liss Radunovich, will help readers learn how to recognize, prevent, and get help for depression and depressive symptoms in older adults. Published by the UF Department of Family, Youth and Community Sciences, July 2007.